SOME FEATURES OF THE "PACKAGE" PRINCIPLE OF CONSIDERATION AND ADOPTION OF LAWS AND OTHER NORMATIVE LEGAL ACTS OF THE REPUBLIC OF KAZAKHSTAN - Konussova, Венера Тулеутаевна; Камал Канаткалиевич; Lyambekova, Арман Каиргельдинова (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The article describes the practices and characteristics of the "package" principle in drafting and adoption of laws and other legal acts. The issue of improving the legislative process is relevant in the light of the extensive social and economic reforms that require adequate and quality legislative regulation. The issue highlighted in the article is important in the light of the "Kazakhstan-2050" Strategy: a new policy of the established state. One of the priorities of this strategy is to define a new mechanism for fast, streamlining development, review and adoption of laws. The main purpose of the presented article is to examine the possibility of "package" principle in lawmaking. The article draws attention to the theoretical developments in this area, as well as an overview of international experience. Particular attention is paid to the experience of the Republic of Belarus, which adopted Guidelines on the application of the principle of package preparation and adoption of draft regulations. Referring to the experience of the Republic of Kazakhstan article contains examples of "package" principle in the adoption of laws. Considering the prospect of the introduction of a "package" principle in legislation system of the Republic of Kazakhstan and taking into account the specifics of Kazakhstan’s legislative process the authors identify possible risks of its implementation. These risks include: planning problems, delays in development time, risk of adoption of the "unpopular" laws and the terms of acceptance. The results can be taken into account in improving process of the legislation of the Republic of Kazakhstan.